Peran Pemerintah Daerah dalam Perizinan Pertambangan Timah dalam Pelaksanaan Reformasi Birokrasi - Enny Agustina (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: Since the existence of regional autonomy, the central government and regional governments have shared their authority in the management of mining mineral resources as regulated in Law No. 22/1999, all authority regarding licensing has been fully delegated to the local government. The study discusses the role of local governments in tin mining licensing in the application of bureaucratic reform and constraints on tin licensing in the application of bureaucratic reform. Methodology: This study uses a normative research method where the method is that the legal approach method is carried out by reviewing all laws and regulations that have relevance or relevance to the legal issues being handled. Result: The results of the research in this study are 1. Regarding the granting of mining permits, since the enactment of Law Number 23 of 2014 concerning regional governments. The authority to issue permits that previously could have been exercised by the Regency/Municipal government was transferred to the Provincial government.